Skeletal Muscle Relaxant Effects of Thymoquinone, the Major Constituent of Nigella sativa - S Parvardeh; M Moghimi (Institue of Medicinal Plants, ACECR, 2015)
Background: It has been shown that Nigella sativa seeds has several pharmacological activities such as sedative effects, decrease in locomotor activity and muscle relaxation. As, many therapeutic properties of Nigella sativa is attributed to its major constituent, "thymoquinone", it might be proposed that Nigella sativa effects on locomotor activity and muscle relaxation is attributed to thymoquinone. Objective: In this study, the effect of thymoquinone on the contractile responses of skeletal muscle has been investigated, using experimental methods. Methods: The chick biventercervicis nerve-muscle preparation was isolated and placed in organ bath. Then, the effects of thymoquinone on contractile responses of skeletal muscle evoked by acetylcholine, KCl, and electrical field stimulation were evaluated through tension recording protocols. Also, muscular strength and motor coordination of mice were evaluated in vivo using traction test and rotarod apparatus following intraperitoneal injection of various doses of thymoquinone. Results: Thymoquinone (40, 80, 100 M) significantly inhibited contractile responses of skeletal muscle to acetylcholine (100 M) and electrical field stimulation, but could not affect contractions induced by KCl (80 mM). Also, thymoquinone (40, 80 mg/kg) significantly decreased the maintenance time of animals in the traction test and rotarod apparatus. Conclusion: The results indicate that thymoquinone may act as a muscle relaxant agent and inhibits the skeletal muscle spasms.